Scaling properties of tidal networks. Issue 6 (4th June 2014) - Jiménez, Mirian; Castanedo, Sonia; Zhou, Zeng; Coco, Giovanni; Medina, Raúl; Rodriguez‐Iturbe, Ignacio
Abstract A new methodology is developed to extract tidal network from hydrodynamic conditions, and use data derived from numerical modeling or field observations to test the hypothesis that tidal networks are characterized by scale‐invariant properties. Different tidal network configurations have been obtained from long‐term numerical simulations in an idealized basin. These simulations show the influence of hydrodynamic conditions (tidal range, TR) and sediment (grain size sediment, D50) on the final configuration of the network. One of the signatures of scale‐invariant behavior is related to the presence of a power law relationship in the probability distribution of geometrical characteristics. For each model configuration and field site, the probability distribution of drainage area and the drainage volume has been calculated, and in both cases tidal networks show scale‐invariant characteristics. After assessing the sensitivity of the results, an energy expenditure analysis shows that tidal basins evolve toward a state with less morphodynamic activity, with a lower energy expenditure compare with the initial state.